2013
DOI: 10.1297/cpe.22.65
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy and Safety of GH in Japanese Children with Down Syndrome Short Stature Accompanied by GH Deficiency

Abstract: In this study, we investigated the effects of GH treatment in children with Down syndrome who had been diagnosed with GH deficiency (GHD). A total of 20 subjects were investigated in this study. Fourteen Down syndrome children (5 boys and 9 girls) with short stature due to GHD were treated with GH at Okayama Red Cross General Hospital, and 6 Down syndrome children (4 boys and 2 girls) with short stature due to GHD were registered in the Pfizer International Growth Database (KIGS). Height SD score (SDS) increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Several reports have found similar differences highlighting short stature as a typical feature in DS, and growth velocity being markedly reduced, mainly between the ages ranging from six months to three years (27). Deficiencies in the secretion of growth hormone (GH) which regulates the production of Insulin-like growth factor (IGFs) have been clearly associated to the marked reduction in speed of growth in young children with DS (28, 29), and consistently with those findings, it has been demonstrated that this phenotype can be normalized with GH therapy (30, 31).…”
Section: Discussionmentioning
confidence: 88%
“…Several reports have found similar differences highlighting short stature as a typical feature in DS, and growth velocity being markedly reduced, mainly between the ages ranging from six months to three years (27). Deficiencies in the secretion of growth hormone (GH) which regulates the production of Insulin-like growth factor (IGFs) have been clearly associated to the marked reduction in speed of growth in young children with DS (28, 29), and consistently with those findings, it has been demonstrated that this phenotype can be normalized with GH therapy (30, 31).…”
Section: Discussionmentioning
confidence: 88%
“…Patients with DS also often show impaired stature that can be linked to a GH deficit (6,19) and can be corrected, at least in part, with the hormone replacement therapy. In subjects that also have CD, the response to the therapy is less satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported on mild subclinical hypothyroidism (19). Precocious puberty was observed in one boy 3.4 yrs after GH treatment initiation (24). In no study was the development of leukemia reported.…”
Section: Adverse Effectsmentioning
confidence: 98%
“…No GH deficiency diagnosis was required in three of the four studies included in the mini meta-analysis (21)(22)(23). A diagnosis of GH deficiency was required in one study included in the meta-analysis (24), as well as in two other studies that could not be included (19,20).…”
Section: Height Outcomementioning
confidence: 99%
See 1 more Smart Citation